Institutional changes in politics - Mieleszko, Anna (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: Institutions are a set of rules of the game, norms and values that constitute a fundamental element of any social and political system. Political institutions are an important object of theoretical considerations and a number of attempts at explanations in political science. in their research, they put more emphasis on the effects of political institutions than on issues related to their genesis and the changes taking place. This article is in the trend of New Institutionalism which focuses on the causal role and the limited ability to design new tools, as well as a strong intention in this area. Aim: The aim of the article is to provide a synthetic overview of the causes and effects of continuity and changes in formal political institutions within the interdisciplinary area — new institutionalism. The research methods used during the preparation of the article include the analysis and criticism of the literature Results: The article focuses on presenting the role of institutions in political life, showing the dysfunctionality of the institutional sphere in the face of pressure from interest groups and the game of political actors. The explanation of these aspects was served by logical constructions and analyzes, primarily of a historical and sociological study, emphasizing the importance of determinants of informal institutions on the durability and institutional change.